Assessing Cerebrovascular Reactivity Abnormality by Comparison to a Reference Atlas. Issue 2 (February 2015) - Sobczyk, Olivia; Battisti-Charbonney, Anne; Poublanc, Julien; Crawley, Adrian P; Sam, Kevin; Fierstra, Jorn; Mandell, Daniel M; Mikulis, David J; Duffin, James; Fisher, Joseph A
Attribution of vascular pathophysiology to reductions in cerebrovascular reactivity (CVR) is confounded by subjective assessment and the normal variation between anatomic regions. This study aimed to develop an objective scoring assessment of abnormality. CVR was measured as the ratio of the blood-oxygen-level-dependent magnetic resonance signal response divided by an increase in CO2, standardized to eliminate variability. A reference normal atlas was generated by coregistering the CVR maps from 46 healthy subjects into a standard space and calculating the mean and standard deviation (s.d.) of CVR for each voxel. Example CVR studies from 10 patients with cerebral vasculopathy were assessed for abnormality, by normalizing each patient's CVR to the same standard space as the atlas, and assigning a z -score to each voxel relative to the mean and s.d. of the corresponding atlas voxel. Z -scores were color coded and superimposed on their anatomic scans to form CVR z -maps. We found the CVR z -maps provided an objective evaluation of abnormality, enhancing our appreciation of the extent and distribution of pathophysiology compared with CVR maps alone. We concluded that CVR z -maps provide an objective, improved form of evaluation for comparisons of voxel-specific CVR between subjects, and across tests sites.